The Effect of Return on Assets, Net Profit Margin, and Debt to Equity Ratio on Stock Returns - Mediaty; Habbe, Abdul Hamid; Yunus (Contemporary Journal of Applied Sciences, 2023)
This study seeks to evaluate the influence of return on assets (ROA), net profit margin (NPM), and debt-to-equity ratio (DER) on the stock returns of manufacturing companies within the consumer goods sector listed on the Indonesia Stock Exchange (IDX) during the period from 2018 to 2021. The investigation encompasses a population of 74 companies within this industry, and employing purposive sampling, a total of 8 companies were chosen as the sample. The research employs a quantitative analysis, specifically adopting an associative research approach. The findings reveal that both ROA and NPM exert a significant individual impact on stock returns, whereas the DER variable does not exhibit a statistically significant influence. Moreover, when considered collectively, the three variables (ROA, NPM, DER) demonstrate a substantial combined effect on stock returns.